Expectations and motivation of the nursing staff - Rymšo, Krystyna; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2020)
Human resources are the main factor determining success, which depends on the capabilities and motivation of an individual. Applying major and additional measures for increasing motivation opens up possibilities to maintain transparency and unanimity of the employee motivation model and encourage the employees to work more efficiently. The aim of the investigation is to examine the system of motivation of the nursing staff. A total of 379 nursing staff was interviewed during the investigation. Having carried out the investigation it became clear that the majority of the research subjects attributed salaries and social guarantees to the important measures of motivation. More than a half (n = 220; 58.1%) of the respondents gave priority to the social guarantee and the possibility to learn. As many as 8.2 per cent of the research subjects pointed out that self-realisation was an absolutely unimportant measure of motivation. In assessing the microclimate at work, the majority (n = 209; 55.1%) of the research subjects stated that they took pride in the work they chose and their communication with the colleagues, and one third of the research subjects had the support of their colleagues and the Head of the unit. One third (35.5 %) of the research subjects gave a positive assessment of the measures of motivation adopted: salaries, and salary supplements. It has been established that as many as 14.2% of the research subjects attributed the review of and the increase in the annual salary, the review and evaluation of the annual work activities and the results achieved to important factors. Conclusions: It has been established that measures of motivation of the nursing staff are not abundant; too little attention is being devoted to the participation of the staff in the activities of the organisation, the prestige of their responsibilities. The nursing personnel attributes salaries, the possibilities to make a career, the evaluation of their work to a very significant factor of motivation, and one third of the respondents consider salary supplements to be of great value. The following measures of motivation of the nursing staff to be applied are as follows: in most cases salaries are reviewed, more than half of the employees are awarded bonuses and extra pays, half of the employees have the possibility to develop their professional qualification. In one sixth of the cases cultural events are organised, and in one fifth of the cases official messages of thanks and citations are given.